STRATEGI PEMENANGAN DAN KOMUNIKASI POLITIK HENDRAR PRIHADI BERBASIS TWITTER - Andika Sanjaya; Intan Triadini (Jurnal Komunikasi dan Kajian Media, 2019)
The general election of Semarang city commonly underlines figures. People choose rationally, smartly, critically, and not easily fooled by politics. The behavior of electing people makes it difficult for political parties to win political elections. This condition is experienced by the Indonesian Democratic Party of Struggle (PDIP) in the 2000s and 2010s. The party electability meets a dilemma when an elected leader faced corruption cases. Hendrar Prihadi as PDIP cadre has succeeded in reversing the situation and won Semarang mayor election in 2015. This descriptive qualitative study explores how Hendrar's political winning strategy. Hendrar has carried out political communication and political campaigns using Twitter. Twitter is used by Hendrar to reach the wider community throughout his voters. Laporhendi is an important hashtag for Hendrar to be shared interactively.